SPEECH ACTS IN BARACK OBAMA SPEECH’S IN ANNOUNCING THE DEATH OF OSAMA BIN LADEN - Atiya Mahmud Hana (Wiralodra English Journal, 2018)
This study aims to observe and describe the use of speech acts by Barack Obama when he announced the death of Osama bin Laden. The writer focuses on illocutionary acts used by Barack Obama. The primary data source is the transcript of Barack Obama’s speech at White House on May 1st, 2011 after the death of Osama bin Laden. The types of illocutionary acts are observed by the writer according to Searle’s Taxonomy of Illocutionary Act. They are representatives, directives, commissives, expressives, and declarations. The result of the study shows that representatives are frequetnly used by Obama in his speech. Representatives are used in 54 utterances (74%); Commissives are used in 11 utterances (15%); Expressives are used in 7 utterances (11%). Barack Obama used none both directive speech acts and declaration speech acts. Representatives are frequently used in Barack Obama speech because the purpose of the speech is to announce the death of Osama bin Laden in Pakistan. The evidence is that most utterances in the transcipt use statements, descriptions, and reports.